Cultural Literacy and Citizenship of Elementary School Students in Bone District - Nurfitrah Ramadhani Alamsyah; Kana Hidayati (JETL (Journal of Education, Teaching and Learning), 2025)
Indonesia as a country has a lot of regional culture and art so it needs to be preserved. Parents Cultural and civic literacy are competencies that need to be mastered amidst changing times. The aim of this research is to determine the cultural and civic literacy skills of elementary school students in Bone Regency. This research is survey research. The subjects of this research were 834 students using purposive sampling techniques. The data analysis technique uses quantitative descriptive analysis. The research results showed that students in the low category were 28% of the total number, students at the medium level were 24% of the total number, then students in the very low category were 22% of the total number. However, students in the very high and high categories respectively account for 16% and 10% of the total number. So special handling is needed for students' relatively low abilities, both by local governments, schools and parents. Cultural and civic literacy are competencies that need to be mastered amidst changing times.